Optimization of postoperative surveillance protocols in upper tract urothelial cancer: A retrospective cohort study - Lindner, Andrea Katharina; Pichler, Martin; Maier, Sarah; Ulmer, Hanno; Gorreri, Thomas; Luger, Anna Katharina; Barth, Dominik A.; Seeber, Andreas; Kocher, Florian; Pichler, Renate (Frontiers in Oncology, 2023)
Upper tract urothelial carcinoma (UTUC) is an aggressive disease, managed by radical or organ sparing surgery. High recurrence rates require early detection and strict follow-up (FU) protocols. Recommendations are assigned to a low level of evidence. Our aim was to identify time to tumour recurrence, analyse temporal relation to recommended FU regimens and provide a critical proposal to further surveillance. This retrospective study included 54 patients receiving radical nephroureterectomy (RNU) in high-risk UTUC and 14 patients assigned to kidney-sparing surgery (KSS) with low-risk disease. FU surveillance protocols consisted of close intervals irrespective of the received type of surgery. In total, 68 patients were included with a median FU of 23 months. Mean overall survival (OS) was significantly shorter in RNU compared to KSS (P = .027). Recurrence in the bladder and/or upper urinary tract (UUT) was 57.1% in KSS and 38.9% after RNU (P = .241). Mean recurrence-free survival (RFS) was significantly shorter in RNU patients compared to KSS (22.4 vs. 47.9 months, P = .013). 76.2% of the recurrences in the RNU group occurred in the first postoperative year. UUT recurrence was diagnosed after a median of 3.0 (RNU) and 25.0 (KSS) months. There is a frequent onset of metastases in the RNU group with 85.7% in the first year compared to the KSS group with 50%. Multivariable regression analysis showed that tumour stage was the parameter independently related to OS (P = .002), RFS (P = .008) and metastasis-free survival (MFS, P = .002). In conclusion, surveillance of UTUC should be adapted to real-time occurrence patterns. Strict imaging protocols are recommended in the first two years irrespective of the method of surgery. As recurrence is equally distributed over years after KSS, cystoscopy should be offered regularly for five years and diagnostic URS for three years. After RNU, cystoscopies should be decreased to yearly intervals after year three. Contralateral UUT should also be examined after RNU.